Non‐Thermoresponsive Decanano‐sized Domains in Thermoresponsive Hydrogel Microspheres Revealed by Temperature‐Controlled High‐Speed Atomic Force Microscopy. Issue 26 (22nd May 2019) - Nishizawa, Yuichiro; Matsui, Shusuke; Urayama, Kenji; Kureha, Takuma; Shibayama, Mitsuhiro; Uchihashi, Takayuki; Suzuki, Daisuke
Abstract: Despite the tremendous efforts devoted to the structural analysis of hydrogel microspheres (microgels), many details of their structures remain unclear. Reported in this study is that thermoresponsive poly( N ‐isopropyl acrylamide) (pNIPAm)‐based microgels exhibit not only the widely accepted core–shell structures, but also inhomogeneous decanano‐sized non‐thermoresponsive spherical domains within their dense cores, which was revealed by temperature‐controlled high‐speed atomic force microscopy (TC‐HS‐AFM). Based on a series of experiments, it is concluded that the non‐thermoresponsive domains are characteristic for pNIPAm microgels synthesized by precipitation polymerization, and plausible structures for microgels prepared by other polymerization techniques are proposed. Abstract : Decanano : By using temperature‐controlled high‐speed AFM, non‐thermoresponsive decanano‐sized domains were found to exist in temperature‐responsive microgels. A comparison to a series of microgels, which differ with respect to cross‐linking density, size, and polymerization techniques, suggested that this heterogeneous structure is characteristic for microgels obtained from precipitation polymerization reactions. This finding will be important for correlating the structures and functions of microgels.